2018
DOI: 10.1002/ehf2.12372
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac expression of neutrophil gelatinase‐associated lipocalin in a model of cancer cachexia‐induced cardiomyopathy

Abstract: AimsCachexia is a severe consequence of cancer. Although cancer‐induced heart atrophy leads to cardiac dysfunction and heart failure (HF), biomarkers for their diagnosis have not been identified. Neutrophil gelatinase‐associated lipocalin (NGAL) is an aldosterone‐responsive gene increased in HF. We studied NGAL and its association with aldosterone levels in a model of cancer cachexia‐induced cardiomyopathy.Methods and resultsRats were injected with Yoshida 108 AH‐130 hepatoma cells to induce tumour. Cachectic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Protein extraction and SDS-PAGE Western Blot analysis. Tissue lysates were prepared as previously described 38,39 . Briefly, 200 mg of liver were homogenized in 300 μL ice-cold lysis buffer (100 mM Tris pH 7,6; 300 mM KCl; 0,1% Triton X 100; 10 μL/mL freshly added protease and phosphatase inhibitor cocktails), centrifuged at 20.000 g for 20 min at 4 °C and supernatant was collected.…”
Section: Extraction and Hplc Analysis Of Flavonoid Compounds In Serummentioning
confidence: 99%
“…Protein extraction and SDS-PAGE Western Blot analysis. Tissue lysates were prepared as previously described 38,39 . Briefly, 200 mg of liver were homogenized in 300 μL ice-cold lysis buffer (100 mM Tris pH 7,6; 300 mM KCl; 0,1% Triton X 100; 10 μL/mL freshly added protease and phosphatase inhibitor cocktails), centrifuged at 20.000 g for 20 min at 4 °C and supernatant was collected.…”
Section: Extraction and Hplc Analysis Of Flavonoid Compounds In Serummentioning
confidence: 99%
“…Several other studies investigated patients with different types of gastrointestinal cancer and reported either a loss of muscle tissue or a loss of both skeletal muscle and adipose tissue mass . In addition, loss of cardiac muscle tissue in cancer cachexia (CC) has been shown in clinical and experimental studies …”
mentioning
confidence: 99%
“…Additionally, KEGG enrichment analysis of the phosphorylated proteins revealed pathways associated with arrhythmogenic right ventricular cardiomyopathy. This may be explained by the elevated levels of aldosterone and neutrophil gelatinase-associated lipocalin that are induced by cancer cachexia ( 56 ).…”
Section: Discussionmentioning
confidence: 99%